Mengungkap Fenomena Potongan Angsuran Murabahah di Perbankan Syariah - Yudhy Muhtar Latuconsina (Journal of Accounting and Investment, 2016)
The purpose of this study is to unveil te phenomenon of Murabahah's discounting payment in shariah banking. This study using interpretive perspective with transcendental phenomenology as a method. The results show that Murabahah's discounting payment is the appeal of Islamic banking to attract prospective customers murabaha financing. In addition, the major determinant factor of the advantages of being given Murabahah's discounting payment. Because of these factors, the Islamic banking policy set Murabahah's discounting payment is only given to to the customers that will end their payment earlier and it helped to get profit realization of shariah banking. In order to minimize the "loss" of the margin (as a profit of Murabahah's), shariah banking using annuity method in the scheme of Murabahah's payment.